1994
DOI: 10.1145/181761.181762
|View full text |Cite
|
Sign up to set email alerts
|

Bug analysis of Pascal programs

Abstract: The paper first looks at issues related to the teaching of programming. Solutions to two programming problems written by participants new to the Pascal programming language are analyzed. The types of bugs which were detected in these programs are then described. Results of such analyses could perhaps help in improving the way programming is taught.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The lack of basic problem solving competence, thinking skills, and transfer of knowledge to other domains is a prominent problem with novice programmers (Mayer, 1981;. Errors in students' programs are commonly related to deficiencies in problem solving strategies and insufficient planning, not syntax (Anjaneyulu, 1994;Scholtz & Weidenbeck, 1992, 1993. Even those studies that uncovered novice difficulties with syntax concluded that more emphasis is needed in teaching planning and design strategies (Soloway et al, 1982) along with software engineering principles (Shackelford & Badre, 1993).…”
Section: Difficulties In Program Developmentmentioning
confidence: 99%
“…The lack of basic problem solving competence, thinking skills, and transfer of knowledge to other domains is a prominent problem with novice programmers (Mayer, 1981;. Errors in students' programs are commonly related to deficiencies in problem solving strategies and insufficient planning, not syntax (Anjaneyulu, 1994;Scholtz & Weidenbeck, 1992, 1993. Even those studies that uncovered novice difficulties with syntax concluded that more emphasis is needed in teaching planning and design strategies (Soloway et al, 1982) along with software engineering principles (Shackelford & Badre, 1993).…”
Section: Difficulties In Program Developmentmentioning
confidence: 99%
“…The lack of basic problem solving competence and thinking skills is a prominent problem with novice programmers. Errors in students' programs are commonly related to deficiencies in problem solving strategies and insufficient planning and design (Hohmann, Guzdial, & Soloway, 1992;Spohrer, 1992;Scholtz & Weidenbeck, 1992Anjaneyulu 1994;Guzdial, Hohmann, Konneman, Walton & Soloway, 1998;Tucker et al, 1998;NRC, 1999;Deek & McHugh, 2000a&b). Both problem solving competence and understanding of the syntax, semantics, and pragmatics of a programming language constitute the foundation skills required to compose, comprehend, reuse, integrate, debug and test, modify and document programs, and students often do not appear to understand the purpose, structure and use of the programming language constructs they study (Soloway, Ehrlich, Bonar, and Greenspan 1982;Bereiter and Scardamalia 1985;Johnson 1990;Ebrahimi, 1994).…”
Section: Introductionmentioning
confidence: 99%